Guided Inquiry Based Students’ Worksheet to Grow Students’ Critical Thinking and Communication Skills - Saputro, Trimo; Herlina, Kartini; Distrik, I Wayan (Universitas Islam Negeri Raden Intan Lampung, 2020)
Weak learning process is one of the problems in education. Therefore, to create the ideal learning process, interactive teaching materials are needed to make student-centered learning.This study aims to describe and analyze teacher and student responses to the development of guided inquiry students worksheets, as well as see their effectiveness in growing critical thinking skills and student communication skills. The research method used is the Mix method with Research and Development type. The instrument used in the form of a feasibility questionnaire and tests of critical thinking skills and communication skills. Based on the research results obtained that the development of worksheets got very valid results from the validators, got very good responses from teachers and students and proven able to foster critical thinking and communication skills.